Do socioeconomic factors affect the prevalence of multiple sclerosis in Iran?. (31st July 2019) - Pakdel, Manizhe; Karin Hedström, Anna; Bidkhori, Mohammad; Hadei, Mostafa; Kazemi Moghaddam, Vahid; Sarmadi, Mohammad; Zohdi, Sara; Marufi, Nilufar
Abstract : Background: A rising trend for incidence of multiple sclerosis (MS) has been observed during the recent years in Iran. Several factors have been investigated as the reason, but socioeconomic determinants have been neglected. The present study aimed to investigate the relationship between Human Development Index (HDI), income and education and MS prevalence in the provinces of Iran. Methods: The data used in this study were obtained from three sources: (a) National Registry of MS for MS prevalence data from 2006 to 2013, (b) Statistical Centre of Iran for demographic, income, and percentage of educated people data, and (c) some previous studies for HDI data. Results: The findings showed high prevalence of MS in the provinces of Iran. Most patients were residents of provinces with a higher socioeconomic level. Significant relationships were found between the prevalence of MS and HDI, income and educational level ( P = .002, P = .006, and P = .001, respectively). Conclusion: Socioeconomic determinants in Iran are different from those in many other countries. It seems that Iranian provinces with a higher socioeconomic level have higher prevalence of MS. Further studies in smaller scale are needed to better understand the relationship between socioeconomic determinants and MS prevalence in the provinces of Iran.